Investigating the validity of the species status of the false codling moth in South African deciduous fruit orchards using mating studies and mtDNA. Issue 5 (14th June 2016) - Mgocheki, N.; Addison, P.
Abstract: The false codling moth is a polyphagous pest of various kinds or fruit, and it has expanded its geographical distribution and host range. The expanding host range could result in subspecies requiring varied pest management options. Laboratory no-choice cross-mating tests were conducted to establish whether Thaumatotibia leucotreta individuals from six areas and three host species, in South Africa, share mating characteristics and belong to the same subspecies or strain. The no-choice cross-mating tests indicated that all individuals in self- and out-crosses readily mated within 24 h with those derived from different hosts and areas. The mt DNA results confirmed that all individuals formed one group or clade. Overall, the results indicate that T. leucotreta individuals from the six areas and three host species in the Western Cape Province and two other provinces in South Africa represent a single genetical species. The results imply that similar control options can be effective across host ranges and distribution areas.